Levinas in Jerusalem: Phenomenology, Ethics, Politics, Aesthetics - Hansel, Joelle (Amsterdam Studies in Jewish Philosophy,, 2009)
A disciple of Husserl and Heidegger, a contemporary of Sartre and Merleau-Ponty, Levinas entirely renewed the way of thinking ethics in our times. In contrast to the whole tradition of Western philosophy, he considered ethics neither as an aspiration to individual perfection, nor as the highest branch in the Cartesian tree of knowledge, but as "first philosophy". By putting into question the priority of Being, by seeing responsibility for the other person as the very structure of subjectivity, Levinas initiated a new understanding of time, freedom or language. This book is a collection of papers given at the International Conference "Levinas in Jerusalem" held at the Hebrew University in May 2002. 2006 marks the Centennial of Levinas's birth. At this occasion, this book gives an overview of the most fecund areas of research in Levinas scholarship. By bringing together historians of philosophy, phenomenologists, specialists in Jewish thought and Talmud, as well as in politics and aesthetics, it relates to his work as a whole, dealing with his philosophical writings and with his Jewish-Talmudic ones. The authors - worldwide renowned scholars and young promising ones - investigate Levinas's relationship to Bergson, Husserl and Heidegger, his conception of Justice and the State, his view of Aesthetics, Eros and the Feminine.